Systematic Literature Review (SLR): An In-Depth Review of Robotic Learning with Quasi-Experimental Methods from Pre-School to High School - Hermanto, Dody; Ardianto, Didit (Journal of Innovative Science Education, 2023)
The increasing presence of robotics in education raises the need for a deeperunderstanding of the effectiveness of robotic learning. This study focuses on asystematic literature review (SLR) of quasi-experimental robotics learning,ranging from preschool to high school. This research aims to detail andinvestigate various quasi-experimental approaches in robotics learning,focusing on the age range from preschool to high school and to understand theimpact on learners after the robotics learning process. This research uses theSLR approach to collect, evaluate, and synthesize current findings in theliterature in the form of articles in reputable international journals spanning theyears 2018-2023 regarding quasi-experimental robotics learning. The analysiswas conducted to identify common trends, weaknesses, and strengths of themethods applied. The results highlighted the variety of quasi-experimentaldesigns used in robotic learning. Based on 15 articles, 10 used pure Quasiexperimental design, and 5 used Mixed Method. The findings provide an indepth understanding of the effectiveness of the various approaches, enablingrobust conclusions to be drawn to improve robotics learning at different levelsof education. This review contributes to the literature by identifying newfindings using quasi-experimental methods in robotics learning and underresearched research variables. Its significance lies in furthering theunderstanding of the variables studied and the effectiveness of robotics learningat different stages of education. This research provides a solid knowledge basefor developing more effective robotics learning strategies, positivelycontributing to the advancement of educational science and providing longterm benefits to society by improving the quality of robotics education.